The Role of Human Capital, Motivation, and Supervisor Sponsorship in Predicting Career Success in the Perspective of Employees in Indonesia - Anne Rumondang Malau; Imelda Sitinjak (LPPM Universitas Terbuka, 2024)
Purpose - This study aims to predicts career success from the perspective of employees in Indonesia by identifying the influential factors. Based on the theory of career mobility systems, human capital and motivation (contest-based) as well as supervisor sponsorship (sponsorship-based) were examined as influential factors. Methodology - The study procedures were carrried out using a quantitative method with a confirmatory design. The sample population comprised 210 employees working in various companies in Indonesia who were selected using the purposive sampling method. In addition, data analysis was carried out using Structural Equation Modeling with LISREL program. Findings - The results showed that human capital and motivation in employees’ settings in Indonesia did not predict career success. However, the hypothesis test revealed that supervisor sponsorship was a significant predictor. Based on these results, employees were encouraged to improve career in companies through leader-member exchange and mentorship. Originality - The results were expected to contribute to the field of human resource management and strategic management, for developing literature on human capital, leader-member exchange, and career mobility systems theory. This study revealed the limitations of human capital and motivation in predicting career success among employees in Indonesia.